Corporeidades em foco: vivências corporais artísticas no IFMA - SILVA, Fernanda Lucia Gadelha (2024)
This study presents an investigation into artistic bodily experiences in the context of the Federal Institute of Maranhão (IFMA), focusing on the Monte Castelo, Maracanã, Historic Center and Rectory campuses. The study aims to analyze artistic bodily experiences, the importance and impact of these educational practices in the training of students involved in educational processes. The research was based on a bibliographical review on the body, corporeality and perception through the senses, from the authors' perspective: David Le Breton (2016, 2016a); Michel Foucault (1997); Maurice Merleau-Ponty(1999); Roy Porter (1997), among others; in addition to field research carried out with teachers, on each of the campuses mentioned and an action research (Thiollent, 1986), on the Historic Center Campus, with students from the 1st year of integrated High School of the technical courses in Visual Art and Events, from October 2022 to January 2023. Data were collected through interviews, questionnaires, logbooks, photographic and audiovisual records, which revealed a trajectory of Art teaching originating at the Federal Technical School, and active over time in this Institution, even in the midst of less political favorable scenarios. Also, there was a significant interest among students in relation to artistic bodily practices, as well as their importance in building knowledge of corporeality, sensitivity and artistic expression. The results point to the need to value and integrate these artistic bodily experiences in a continuous and complementary way to conventional art classes, aiming to enrich the students' educational experience and promote integral development.